"The prayers of others helped": Intercessory prayer as a source of coping and resilience in Christian African American families. Issue 4 (2nd October 2018) - Skipper, Antonius; Moore, Travis James; Marks, Loren
ABSTRACT: Married African American families are perceived as highly religious; however, they are often underrepresented in research studies involving prayer. This study used qualitative interviews to examine intercessory prayer as a perceived source of strength and resilience for 33 heterosexual, highly religious African American families identifying as Christian. Data were analyzed using open coding and Numeric Content Analysis. The following themes were identified: (a) Interceding Prayers Build Personal Strength, (b) Interceding Prayers Strengthen Marital Bonds, and (c) Interceding Prayers Unite Communities. Narratives are offered to support each theme and social work implications are discussed.